HIV-associated motor neuron disease: HERV-K activation and response to antiretroviral therapy. (25th October 2016) - Bowen, Lauren N.; Tyagi, Richa; Li, Wenxue; Alfahad, Tariq; Smith, Bryan; Wright, Mary; Singer, Elyse J.; Nath, Avindra
Abstract : Objective: To determine whether there is activation of human endogenous retrovirus K (HERV-K) in amyotrophic lateral sclerosis in HIV infection and whether it might respond to treatment with antiretroviral drugs. Methods: In this case series, we present 5 patients with HIV infection who subsequently developed motor neuron disease involving both upper and lower motor neurons. We monitored HERV-K levels in plasma of 4 of these patients. Results: Three patients who received antiretroviral therapy had reversal of symptoms within 6 months of onset of neurologic symptoms and the other 2 had slow neurologic progression over several years. Three patients in whom the levels were measured at onset of neurologic symptoms showed elevated HERV-K levels that responded to optimization of antiretroviral therapy for CNS penetration. Conclusions: Thus, motor neuron disease in individuals with HIV infection may a treatable entity, but early treatment with CNS-penetrating antiretroviral therapy may be necessary. Monitoring of HERV-K levels may help guide treatment.